Vitamin D3 requirements and relative bioavailability for starter male White Pekin ducks fed either cholecalciferol or 25-hydroxycholecalciferol - Jing Tang; Lei Zhuang; Yating Li; Dawei Luo; Zhanbao Guo; Shuaiqin Wang; Jindang Cao; Mingkai Wang; Zhengkui Zhou; Ming Xie; Shuisheng Hou (Poultry Science)
The objectives were to investigate effects of various concentrations of dietary vitamin D3 (VD3) or 25-hydroxycholecalciferol (25-OH-D3) on growth performance, VD3 status, calcium (Ca) metabolism, and tibia mineralization of starter male White Pekin ducks, and dietary requirements and relative bioavailability of these two compounds. One-day-old male White Pekin ducks (n = 624) were assigned to 13 dietary treatments, including 6 added VD3 concentrations (100, 200, 400, 800, 1200, and 2000 IU/kg), and 2 vitamin D3 sources (VD3 and 25-OH-D3), plus a negative control (no vitamin D3 supplementation) for 21 days. Each group had 6 replicate pens of 8 birds per pen. At 21 days of age, growth performance, carcass traits, plasma 25-OH-D3 and Ca content, and tibia mineralization were examined. There was a high incidence of leg disease and mortality in ducks fed the control diet; however, those negative effects were avoided by adequate VD3 or 25-OH-D3 supplementation. Ducks in the negative control group had the lowest body weight, average daily weight gain (ADG), average daily feed intake (ADFI), breast muscle percentage, plasma 25-OH-D3, plasma Ca, and tibia indices (weight, diameter, ash, density, tibia mineral, strength) (P < 0.05), with all these end points enhanced linearly or quadratically as dietary VD3 or 25-OH-D3 increased (P < 0.05). Furthermore, at 100 or 200 IU/kg, ducks fed 25-OH-D3 had greater body weight, ADG, ADFI, plasma Ca, plasma 25-OH-D3, tibia weight, tibia diameter, tibia ash than those fed VD3 (P < 0.05), indicating 25-OH-D3 was more effective in stimulating growth, Ca absorption, and tibia mineralization. For growth performance, breast muscle percentage, plasma Ca, and tibial indices of starter male Pekin ducks, the VD3 requirements were 281 to 633 IU/kg, whereas 25-OH-D3 requirements were 119 to 395 IU/kg. Based on slope ratio comparisons from multiple linear regressions of plasma 25-OH-D3, bioavailability of 25-OH-D3 was 186% relative to cholecalciferol.